RANCANG BANGUN APLIKASI BELAJAR ARAB UNTUK ANDROID MENGGUNAKAN JETPACK COMPOSE DAN KOTLIN - Dzulqarnain, Fahmi; Tukino, Tukino (Universitas Putera Batam, 2023)
Indonesia has the world's largest Muslim population, so learning Arabic is quite important and is widely practised throughout the country. However, learning Arabic is often done with less efficient and effective methods due to the problem of language differences that are quite far from the Indonesian Language. These differences can be seen in sound or phonetic systems, letters, grammar, and vocabulary management. This research was conducted with the aim of designing and building a system in the form of a simple language game with self-dictionary to overcome the problems faced by Indonesians who have or will learn Arabic. This Arabic learning app will be designed to be interactive and fun for Arabic learners in Indonesia with the default app instruction language also using The Indonesia Language. The design method will use the Agile method. The result of designing and building this Arabic Learning app is successful because all of the feature test conducted has been passed.